1997
DOI: 10.1108/eb021047
|View full text |Cite
|
Sign up to set email alerts
|

The barriers to entry into the PFI market

Abstract: This paper reports early results of a study of construction contractors and their experiences of the PFI market. Utilizing material from semi-structured interviews with three categories of construction contractor, small, medium and large, consideration is given to the barriers to entry which contractors face when approaching the PFI market. The paper highlights six barriers of entry: lack of appropriate skills; high participation costs; high project values; high risk; lack of credibility and contacts; and dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…These full-service firms have the size, experience in general project management, reputation, and financial capacity to take a lead role in multiple public-private partnership bids and to obtain external investments (Ezulike, Perry, and Hawwash 1997). Put differently, full-service firms in each sector have experience working in contexts of complex project ecologies that require the coordination of numerous subcontractors and reciprocally related tasks.…”
Section: The Network Centrality Of Integrated Companiesmentioning
confidence: 99%
“…These full-service firms have the size, experience in general project management, reputation, and financial capacity to take a lead role in multiple public-private partnership bids and to obtain external investments (Ezulike, Perry, and Hawwash 1997). Put differently, full-service firms in each sector have experience working in contexts of complex project ecologies that require the coordination of numerous subcontractors and reciprocally related tasks.…”
Section: The Network Centrality Of Integrated Companiesmentioning
confidence: 99%
“…In construction the methods used for tendering and procurement of projects are important determinants of the level and form of competition in the industry. The emergence of the one stop supplier, the global firm, for large private and public projects, with their demand for capacity, technical capability and capital, has placed these projects out of reach of the conventional contractors, (see also Ezulike et. al.…”
Section: From a Small Scale Australian Contractor To A Global Giant Some Illustrationsmentioning
confidence: 99%
“…The level of risks involved in PFI contracts and the amount of finance required can be a barrier to entry for smaller private companies (Ezulike et al 1997). Owen and Merna (1997) also found that risk allocations early on were perceived to be unfair to private sector partners.…”
Section: 121risks In Partnership Arrangements: Practical Versus mentioning
confidence: 99%